Metal–organic framework derived Os-doped NixP/N-doped carbon composite nanosheet arrays toward boosting methanol oxidation into value-added chemicals coupled with hydrogen production. Issue 35 (19th August 2022) - Duan, Zhongyao; Ren, Tianlun; Mao, Qiqi; Yu, Hongjie; Deng, Kai; Xu, You; Wang, Ziqiang; Wang, Liang; Wang, Hongjing
Abstract : An Os–Ni x P/N–C/NFIIOs–Ni x P/N–C/NF electrolyzer has been constructed for simultaneous H2 generation and formate electrosynthesis. Abstract : Reducing the high energy of water splitting caused by a sluggish oxygen evolution reaction (OER) is essential, but still a challenge. Replacing the anodic OER with a thermodynamically favorable organic upgrading reaction not only reduces the operating voltage, but also produces value-added chemicals, which is regarded as a win–win strategy. In this work, MOF-derived Os-doped Ni x P/N-doped carbon composite nanosheet arrays on nickel foam (Os–Ni x P/N–C/NF) are fabricated as a bifunctional catalyst for oxidizing methanol to value-added formate while simultaneously facilitating H2 production. Taking advantage of synergistic structural and compositional properties, the obtained Os–Ni x P/N–C/NF exhibits high faradaic efficiency for generating anodic formate (92%) and cathodic H2 (100%). Moreover, the two electrode systems only need 1.43 V to achieve an electrolytic current density of 10 mA cm −2 in 1.0 M KOH with 1.0 M methanol.